Nelson's complete book of stories, illustrations & quotes - Morgan Robert J (Nashville T. Nelson Publishers, 2000)
"The ultimate contemporary resource for speakers." -- Cover.
Keywords: Christian life -- Anecdotes. Conduct of life -- Anecdotes. Christian life